Voluntary Disclosure Programs : Design, Principles, and Implementation Considerations - Benedek, Dora.; Grote, Martin; Jackson, Grace; Markevych, Maksym; Waerzeggers, Christophe (Washington, D.C. : International Monetary Fund, 2022)
This note explores the conditions, design elements, and implementation considerations of a successful voluntary disclosure program (VDP), including its compliance with anti-money laundering/combating the financing of terrorism (AML/CFT) international standards. The note emphasizes that such a program must be offered in the context of a considerably strengthened and credible enforcement capacity-one that is explicitly publicized to taxpayers-to avoid undermining tax morale.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: National Government Expenditures and Related Policies; Public Finance; Tax Evasion and Avoidance